The key role of public health in renovating Italian biomedical doctoral programs - Palandri, Lucia; Urbano, Teresa; Pezzuoli, Carla; Miselli, Francesca; Caraffi, Riccardo; Filippini, Tommaso; Bargellini, Annalisa; Righi, Elena; Mazzi, Davide; Vigezzi, Giacomo Pietro; Odone, Anna; Marmiroli, Sandra; et al. (Annali di Igiene Medicina Preventiva e di Comunità, 2024)
Background. A key renovation of doctoral programs is currently ongoing in Italy. Public health and its competencies may play a pivotal role in high-level training to scientific research, including interdisciplinary and methodological abilities. Methods. As a case study, we used the ongoing renovation of the Clinical and Experimental Medicine doctoral program at the University of Modena and Reggio Emilia. We focused on how the program is designed to meet national requirements as well as students’ needs, thus improving educational standards for scientific research in the biomedical field, and on the specific contribution of public health and epidemiology in such an effort.Results. The renovation process of doctoral programs in Italy, with specific reference to the biomedical field, focuses on epidemiologic-statistical methodology, ethics, language and communication skills, and open science from an interdisciplinary and international perspective. In the specific context of the doctoral program assessed in the study and from a broader perspective, public health appears to play a key role, taking advantage of most recent methodological advancements, and contributing to the renovation of the learning process and its systematic quality monitoring.Conclusions. From a comparative assessment of this case study and Italian legislation, the key role of public health has emerged in the renovation process of doctoral programs in the biomedical field.